Associations of functional disability and behavioural risk factors with social participation of older adults: a cross-sectional analysis from the Canadian Longitudinal Study on Aging. Issue 1 (19th January 2022) - Raina, Parminder; Ali, Muhammad Usman; Joshi, Divya; Gilsing, Anne; Mayhew, Alexandra; Thompson, Mary; Griffith, Lauren E
Abstract : Objectives: To examine: (1) the associations of functional disability and behavioural risk factors with social participation; and (2) whether the association between functional disability and social participation is modified by co-occurrence of behavioural risk factors. Design: A cross-sectional analysis of data from the Canadian Longitudinal Study on Aging. Setting: A national stratified sample of 51 388 individuals living in the 10 Canadian provinces at the time of baseline data collection (2011–2015). Participants: Participants included men and women aged 45–85 years and residing in the communities in the 10 Canadian provinces. Outcome measures: Social participation was assessed using frequency of participant involvement in eight different social activities in the past 12 months. Responses for each category were converted into number of days per month. Total social participation score (range: 0–180) was based on summing frequencies over all eight activities representing number of social activities per month. Results: Functional disability was associated with participating in fewer social activities (difference in mean total social participation score, b=−1.1, 95% CI −1.5 to –0.7). In comparison to no behavioural risk factors, presence of any one (b=−2.7, 95% CI −3.1 to –2.3), any two (b=−4.6, 95% CI −5.0 to –4.2), any three (b=−6.3, 95% CI −6.8 to –5.9) and all four (b=−7.8, 95% CI −9.0 to –6.6) behavioural risk factors was associated with lower social participation. The association between functional disability and social participation was modified by the presence of behavioural risk factors with the lowest social participation observed for adults with disability and all four behavioural risk factors (b=−4.3, 95% CI −7.5 to –1.2). Conclusions: Individuals with functional disabilities and behavioural risk factors are more likely to experience restrictions in social participation. Public health interventions that encourage healthy lifestyle behaviours may help mitigate the impact of functional disabilities on social participation in the ageing population.